Swertia kashmirensis subsp. darii (Gentianaceae), a new taxon from Kashmir Himalaya, India - Islam, Tajamul; Rasray, Bilal A.; Khuroo, Anzar Ahmad; Ganie, Aijaz H.; Mugal, Muzamil Ahmad; Nawchoo, Irshad A. (Phytotaxa, 2024)
Swertia kashmirensis subsp. darii (Gentianaceae), a new taxon from Kashmir Himalaya, India is described here with description and photographic illustrations. The new taxon resembles in few morphological characters with congeneric S. kashmirensis, but differs clearly in having basal leaves with apices acute, petals elliptic-oblong, apices obtuse with an apical notch, whitish adaxially and purplish with dull whitish margins abaxially, size of nectaries and fimbriae, carpel ovoid, anthers ovate, capsule ellipsoid, seeds brownish, round with wings narrow.